(untitled) (Palíndromo, 2016)
The Japanese animations, also known as anime, are popular audiovi- sual productions in the West, especially in Brazil. Created for public of different ages and addressing various topics, ani- mes become interesting research sour- ces to understand discourses and re- presentations conveyed socially. In this sense, this article aims to analyze how an ideal of justice is represented in the Death Note anime (from the character Light Yagami) that has an engaging plot about questions as murder and revenge. Thus, since the junction between image and sound is crucial for the purposes of impact on the anime audience, we will use the theory of audiovision proposed by Michel Chion, in order to demonstrate how these elements generate meanings together, in order to supplementing sen- ses and directing the perception of the spectators.